Свет чужого солнца: [роман] / Нэнси Кресс - Кресс Нэнси (Координаты чудес, 1995)
Экземпляры: ф.22 (1996) / Инвентарный номер: 38892 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: К 80 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-445